EDUKASI GIZI BERBASIS PIRING T SEBAGAI UPAYA PENCEGAHAN MASALAH DIABETES TIPE 2 - Nazhif Gifari; Rachmanida Nuzrina; Putri Ronitawati; Mury Kuswari; Maya Fernandya (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2026)
The prevalence of type 2 diabetes mellitus has increased, particularly among the elderly population, whose general nutrition knowledge remains limited. This community service program aimed to improve the knowledge and skills of Posbindu cadres through education using the Diabetes Plate (Piring T) media. The methods included socialization, counseling, and training involving 30 Posbindu cadres in Jakarta. Evaluation was conducted using pre-test and post-test assessments, as well as observation of cadres’ ability to re-explain the material. The results demonstrated an increase in the mean knowledge score from 77.6 to 86.4 (an improvement of 10.8 points or approximately 13.9%). In addition, around 80% of participants were able to understand and apply balanced meal portion concepts using the Diabetes Plate, as evidenced by food documentation submitted during the program. Therefore, this community service program enhanced cadres’ capacity to independently deliver nutrition education and has the potential to improve the quality of Posbindu services, contributing to the prevention of type 2 diabetes.